The lived experiences of sexual minority Christian faculty at Midwestern public institutions. - Hinrichs, Diane Elaine (Kansas State University, 2019)
Colleges and universities are recognizing the deficient representation of minoritized faculty. In response to the growing number of minoritized students and the desire to provide a more diverse experience to all students in higher education, institutions have created many programs and initiatives to attract and hire a more diverse faculty (Wilson, 2016). Research has provided much evidence on the experiences of many minoritized faculty but has failed to examine the experiences of sexual minority Christian faculty. In this qualitative study, I investigated the lived experiences of sexual minority Christian faculty at Midwestern public institutions. The study sought to answer the following research questions: What are the lived experiences of sexual minority Christian faculty working at Midwestern public institutions of higher education? Does the identity of sexual minority Christian faculty influence their pedagogy, institutional and departmental identity, student engagement and other areas of faculty work? Utilizing interviews and a phenomenological approach, I sought to gather new information on the essence of being a sexual minority Christian faculty member and how the intersectionality of those identities manifests itself in their work. Five faculty members who identified as sexual minority Christian faculty met the criteria of the study and agreed to participate. Based on the findings of this study, the essence of being a sexual minority Christian faculty member at a Midwestern institution is nuanced with experiencing a wide array of institutional acceptance both from inside and outside of their department and college. For most, but not all, being a sexual minority is a more salient identity than their identity as a Christian, but through attributive strategic self-disclosure, they most often present that identity on campus through mention of their spouses or partners without hesitation in everyday conversation. However, they all acknowledge the necessity – when not in the safe-haven of academia – to continually evaluate their openness and language during conversations with strangers. Most of the participants sought involvement in a Christian congregation, but all of those who did, had experiences of marginalization and feeling “less than.” While most of these experiences were not overt discriminatory actions or disparagements, they still impacted how the participants viewed the church. Those who had ultimately become involved an open and affirming congregation felt accepted and relieved. Involvement in open and affirming congregations was immensely satisfying to those who chose such involvement. The findings of this study have the potential to assist campus administrators in examining the climate of their institution, colleges and departments to identify ways to develop more inclusive and welcoming environments for sexual minority Christian faculty members.
Keywords: Sexual minority; LGBT; Faculty; Christian; Qualitative